Pengaruh Kemiskinan, Pertumbuhan Ekonomi, dan Pengeluaran Pemerintah Terhadap Islamic Human Development Index (I-HdI) di Indonesia - Abd Halim Dalimunthe; Imsar Imsar (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Conventional measurement of economic development is considered not to reflect social justice and does not represent social welfare. Various criticisms and perspectives on measuring economic development have emerged. One of them is the Islamic economic perspective that uses the measurement of human welfare and development through the Islamic Human Development Index or often abbreviated as I-HDI. I-HDI includes elements of social welfare that have often been overlooked. The purpose of this study was to determine the value of I-HDI and the effect of several conventional economic variables on the I-HDI. The variables in question are poverty, economic growth, and government spending. The data used in this study is secondary data derived from the publications of BPS and the World Bank. This research is a descriptive quantitative research. The data used is time series data from 2010-2020. The analysis was performed using multiple linear regression. The results showed that I-HDI Indonesia has increased every year although it is still relatively low. Poverty and economic growth have a negative effect on I-HDI and government spending has a positive effect. So, it can be concluded that human development in Indonesia is still relatively low and one of the factors that can increase this is government spending.